Prognostic factors for early-stage epithelial ovarian cancer, treated with adjuvant carboplatin/paclitaxel chemotherapy: A single institution experience - Bamias, A.; Karadimou, A.; Soupos, N.; Sotiropoulou, M.; Zagouri, F.; Haidopoulos, D.; Thomakos, N.; Rodolakis, A.; Antsaklis, A.; Dimopoulos, M.A. (Gynecologic Oncology, 2011)
Objective: Early-stage epithelial ovarian cancer represents a prognostically heterogenous group. We studied prognostic factors in patients treated with adjuvant paclitaxel/carboplatin chemotherapy. Methods: Data was extracted from 147 patients with FIGO stage IA/IB, grade 2/3 or stage IC/IIA (any grade) who underwent primary surgery followed by paclitaxel/carboplatin chemotherapy. Results: Median follow-up was 88 months. Ten-year relapse-free (RFS) and disease-specific survival (DSS) were: 81% (95% confidence interval [CI]: 73-89) and 81% (95% CI: 73-89). On multivariate analysis, non serous histology was associated with reduced risk for RFS (0.294, 95% CI: 0.112-0.577, p = 0.001) and DSS (0.194, 95% CI: 0.075-0.504, p = 0.001), while high-risk category (stage IC/IIA and grade 2/3) with increased risk for RFS (3.989, 95% CI: 1.189-13.389, p = 0.009) and DSS (3.989, 95% CI: 1.064-16.386, p = 0.038). The combination of histology and grade identified 3 groups with distinctly different 10-year RFS and DSS rates (p < 0.001): grade 1 (100% and 100%), non-serous grade 2/3 (83% and 86%) and serous grade 2/3 (60% and 60%). Conclusions: Serous histology is an adverse prognostic factor in early-stage ovarian cancer treated with adjuvant paclitaxel/carboplatin. Risk stratification according to histology and grade is a useful discriminator of prognosis and can be used in the design of future studies. © 2011 Elsevier Inc. All rights reserved.
Keywords: Early stage; Ovarian cancer; Prognostic factors; Serous; Tumor type